Position and Optimization of the Economic Benefits of Zakat for Empowerment of the People - Jefik Zulfikar Hafizd (Rumah Moderasi Beragama of Syekh Nurjati State Islamic Institute Cirebon, 2021)
Humans are creatures who need each other. Human destiny does not all have economic adequacy, but there are also those who have shortcomings. Zakat is a means of distributing wealth from the rich to the needy. This research is a literature study using the descriptive analysis method to examine the position of zakat in sharia economic perspective and how to optimize the economic benefits of zakat. The scope of the discussion in this study includes the concept of zakat. position of zakat, zakat management, benefits of zakat, optimization of productive zakat, as well as challenges and opportunities for zakat development. Sources of research data were obtained from various references that include books, journals, laws and regulations, and other related references. The results of this study state that zakat is worship that has a major influence on the human economy. The strategy for developing zakat can be done through da'wah, utilization of information technology, and increasing productive zakat. Zakat has a very strategic function in the context of the economic system, namely as an instrument of wealth distribution. Public awareness is an important key in growing zakat itself. The findings of this study are productive zakat can be done for the construction of mosques, schools, da'wah buildings, to factories with qiyas as asnaf fii sabilillah. Zakat funds on the development are handed over to people who qualify as fii sabilillah as zakat mustahik.